Efficient colloidal route to pure phase kesterite Cu2ZnSnS4 (CZTS) nanocrystals with controlled shape and structure. (July 2018) - Jain, Shefali; Chawla, Parul; Sharma, Shailesh Narain; Singh, Dinesh; Vijayan, N.
Abstract: This work reports the synthesis of varied shaped Cu2 ZnSnS4 (CZTS) nano inks in a most stable kesterite phase via a hot injection colloidal route. CZTS nanoparticles of varied shape were synthesized by using various capping ligands with the introduction of butylamine as a new capping ligand and two different sulfur precursors respectively. The shape of the as-synthesized kesterite CZTS nanocrystals can be well controlled in the form of nanofibers, spherical nanoparticles, nano hexagons, nanotriangles, and nanodiscs. A detailed analysis of the effects of various capping ligand and sulfur source on reaction conditions to obtain pure phase kesterite CZTS nanocrystals for different shapes is explained using LaMer's diagram. It has been found that the choice of sulfur precursor also plays an important role in determining the symmetry and orientation of the plane of the CZTS nanocrystals. Due to different morphology and capping ligands present on the surface, diverse surface properties were obtained which was confirmed by contact angle measurements. The variation in the band gap was also found with changes in morphology of kesterite phased CZTS nanoparticles. Due to variations obtained in band gap, changes in I-V characteristics were also observed which may leads different CZTS nanoparticles to have their potential applications in different regime other than photovoltaics like sensors, photocatalysis etc. Graphical abstract: The molecular interaction of different capping ligands involved in the synthesis of Cu2 ZnSnS4 nanoparticles has been explained using LaMer's Plot. Highlights: Synthesis of CZTS nanoparticles using colloidal route and its explanation on the basis of LaMer's Plot. Synthesis of different shaped CZTS nanoparticles by varying capping ligands and Sulfur sources. Various shapes obtained due to different preferred orientations of different surfactant. Band gap, wettability and I-V Characteristics were explained for different CZTS nanoparticles.